Hidradenitis suppurativa - Papadopoulos, A... J. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Hidradenitis suppurativa is a chronic and often disabling disease characterized by intermittent periods of inflammation and abscess information in apocrine sweat gland-containing skin. Various therapies have been implemented in its treatment with variable results. Pathogenesis, histopathology and therapy of this disease are reviewed.
Keywords: Apocrine glands; dermatologija; Folliculitis; Hidradenitis suppurativa; kožne bolezni; kronične bolezni; Sweat gland diseases